POWER AND RESISTANCE IN TA-NEHISI COATES’S THE WATER DANCER AND KAWAI STRONG WASHBURN’S SHARKS IN THE TIME OF SAVIORS - Rasheed , Khorsheed; Fahmi , Ismael; Abdulkarim, Chiad (Humanities Journal of University of Zakho, 2025)
This article is an attempt to studiously explore both power and resistance and their interactions and relations along with their impacts and functions in the selected novels; Ta-Nehisi Coates’s The Water Dancer (2019), and Kawai Strong Washburn’s Sharks in the Time of Saviors (2020). It aims to focus on the way of incorporating magical elements in the narratives to redefine power dynamics in various prospective and it serves to create a magical realism that shapes the new mechanism of resistance. Both power and resistance, in this article, are conceptualized to illustrate the existing power as well as reversed forces in the life of main characters in the novels. Besides, this article employs particular concepts such as knowledge, power, and discipline as defined and explained by Michel Foucault (1926–1984) which are relevant to power and resistance. In the narrative, Ta-Nehisi Coates represents Hiram’s, the protagonist of the story, ability of conduction as a supernatural power that is stimulated by the power of memory in the novel. Throughout the magical element, the author creates an alternative reality that memory and trauma used as a source for equality and liberation. Similarly, Washburn utilizes Nainoa’s, the protagonist, miraculous ability of healing as a reversed power in a nature of resistance against existed social forces in the text. Nainoa’s supernatural ability is deeply linked to Hawaiian mythology in which it serves as a metaphorical force for recovering cultural identity and opposing existed forces that marginalize indigenous Hawaiians. Finally, this article concludes that both novels serve the function of the use of magical power in the two powers in terms of power and resistance. The authors portray power through oppressive systems, by the magical elements, both offer alternative pathways toward self-liberation. It emphasizes on inseparableness of power and resistance, besides, it highlights that magical realism provides a powerful mechanism to reimagine reality encountering social justice and equality in contemporary literature.